The Effect of R&D Alliance Diversity and Network Position on Firm Innovation Performance: Evidence from the Emerging Biotechnology Industry. (November 2017) - Wang, Chun Hsien; Quan, Xiaohong Iris
Despite increasing attention to the role of diverse alliances in emerging market, few studies have explicitly explored the roles of environment and network position on diverse R&D alliances. This study investigates how environment and network position interact with diverse R&D alliances to affect firm innovation performance. Specifically, we examine the moderating effects of technology uncertainty, market uncertainty, network centrality position and competitive intensity. The findings from a survey of 144 biotechnology firms indicate that diverse R&D alliances have a positive effect on firms' innovation performance, and these effects are moderated by environmental factors and alliance network position. The overall R&D alliance network was also examined to understand a broad variety of collaboration patterns of emerging biotechnology firms.